Design, Synthesis, and Antimicrobial Activity Evaluation of New Developed Compounds via Introducing of 3, 4-Dimethyl Maleimidyl Sulfonamide Moiety - Akol, Raghad Naeem; Al-Azzawi, Ahlam Marouf (Iraqi Journal of Science, 2025)
The present study focuses on creating and engineering novel compounds based on five established medications: Sulfamethoxazole, Ampicillin, Cefotaxime, Sulfamethazine, and Trimethoprim. The research involves incorporating a biologically active component, specifically the 3,4-dimethyl maleimidyl sulfonamide group, into these drug molecules to produce the target compounds. Many steps were performed on this target; the first one involved a reaction between 3,4-dimethyl maleic anhydride and aniline to produce compound (1) N-phenyl-3,4-dimethyl maleimide which reacts with chlorosulfonic acid in the second step producing compound (2) 4-[N-(3՝,4՝-dimethyl maleimidyl)phenyl sulfonyl chloride. The third step involved compound (2) reaction with the selected drugs, producing the target- developed compounds (3-7). The newly synthesized compounds were tested for their antibacterial and antifungal activities. Results showed they exhibit high levels of activity against both bacteria and fungi.